EKSPLORASI EKSTRAK TUMBUHAN SEBAGAI PEWARNA ALAMI BATIK PADA KAIN MORI PRIMISSIMA DENGAN VARIASI ZAT FIKSASI - Bestari, Qorina; Jupriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the increasing interest in natural batik dyes as an environmentally friendly alternative, yet it remains constrained by the limited color variations and inconsistency of dyeing results. This study aims to explore plant extracts as natural dyes for batik on Primissima mori fabric with various fixationagents and to analyze their effects on color characteristics and colorfastness. The research method employed a descriptive qualitative approach through exploratory experiments using three types of plant extracts (Syzygium myrtifolium fruit, Curcumaxanthorrhiza rhizome, and their combination) as well as three variations of fixation agents (alum, lime, and ferrous sulfate) on Primissima mori fabric. The results showed that Syzygium myrtifolium fruit extract produced reddish-purple to browncolors, Curcuma xanthorrhiza extract produced yellow to yellowish-orange colors, and their combination produced transitional yellowish-orange colors. The use of alum fixation produced the brightest colors closest to the original extract color, limeproduced paler colors, while ferrous sulfate produced the darkest colors with a saddening effect. The color brightness levels in descending order were alum, control, lime, and ferrous sulfate. This study concludes that the type of plant extract and variations of fixation agents significantly influence the characteristics, variations,and brightness levels of natural batik colors on Primissima mori fabric.